2022
DOI: 10.1126/sciadv.abo1874
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive point-of-care biochemical sensor based on metal-AIEgen frameworks

Abstract: Point-of-care (POC) biochemical sensors have found broad applications in areas ranging from clinical diagnosis to environmental monitoring. However, POC sensors often suffer from poor sensitivity. Here, we synthesized a metal-organic framework, where the ligand is the aggregation-induced emission luminogen (AIEgen), which we call metal-AIEgen frameworks (MAFs), for use in the ultrasensitive POC biochemical sensors. MAFs process a unique luminescent mechanism of structural rigidity-enhanced emission to achieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 82 publications
(81 reference statements)
0
40
0
Order By: Relevance
“…Cellulose paper-based microfluidics can handle 0.1–100 μL of liquid through millimeter-scale fluidic channels [ 119 ]. As one of the popular applications of paper-based materials, lateral flow assay (LFA) is a user-friendly diagnostic tool [ [120] , [121] , [122] , [123] , [124] ].
Fig.
…”
Section: Chip Classification and Structurementioning
confidence: 99%
“…Cellulose paper-based microfluidics can handle 0.1–100 μL of liquid through millimeter-scale fluidic channels [ 119 ]. As one of the popular applications of paper-based materials, lateral flow assay (LFA) is a user-friendly diagnostic tool [ [120] , [121] , [122] , [123] , [124] ].
Fig.
…”
Section: Chip Classification and Structurementioning
confidence: 99%
“…569 Jiang et al reported 1,1,2,2tetra(4-carboxylphenyl)ethylene (TCPE)@Zr MAFs and their application in POCT sensors. 570 By adding regulators, blueemissive MAFs were synthesized with different morphologies and sizes, and transparent MAFs@hydrogel composites for stable and ultrasensitive POCT were produced. Compared to the other fluorescent MOFs, the sensitivity of MAFs was enhanced about 1000 times.…”
Section: Virus Detectionmentioning
confidence: 99%
“…, which has attracted great attention from researchers. 34–37 Studies have found that MOFs have a wide range of application prospects, which not only achieve great success in gas storage, 38 separation, 39 catalysis, 40,41 energy 42,43 and sensing 44,45 but also show unparalleled potential in biomedical applications. 46–48…”
Section: Introductionmentioning
confidence: 99%